The Effect of Using Storytelling Techniques Adopting Thai Folktales to Enhance Students Vocabulary in Thai EFL Elementary School - Asmara, Candra Hadi; Ma’rifah, Ulfatul; Fitria, Anisa Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
These objective aim to provide a comprehensive understanding of the effectiveness and potential benefits using storytelling techniques drawn from Thai folktales in enhancing students vocabulary in Thai elementary school. By achieving these objective, the study aims to contribute valuable insights to engage education practices and provide evidence based recommendation for educators seeking to improve vocabulary instruction in EFL contexs. The method used was quantitative, quasi-experimental as a research design; The method and instrument involved numerical measures and statistical quantitative. In this study, we will use two classes: an experimental class for grades IVA and IVB as a control class. The writer will conduct eight meetings: two meetings for conducting the pretest and posttest for the experimental class and control class; Two meetings for implementation to give the treatments in the experimental class; Two meeting for not implementing the control class; And the last two meetings will focus on assessing the performance of storytelling for those two group. The data showed that the mean score of the pretest in the experimental class was 67,5, while the mean score of the pretest in the control group class was 65. Meanwhile, the score of the posttest in the experimental class was 77,5, and the mean score of the posttest in the control group class was 67,9. From the data analysis, we can conclude that the vocabulary of the students using storytelling techniques and adopting Thai folktales in the experimental class that was given by the teacher.